Surgery for Low Back Pain - Szpalski, Marek; Gunzburg, Robert; Rydevik, Björn L.; Le Huec, Jean-Charles; Mayer, H. Michael (Springer Berlin Heidelberg : Imprint: Springer, 2010)
Low back pain is a very common problem. Various treatments are available, but surgery has acquired increasing importance. In the United States, low back pain is now the principal reason for spinal surgery, and the number of procedures performed for this reason is similar to the number of total hip replacements. Consequently there is a need for careful evaluation of the possible surgical approaches to low back pain, with detailed appraisal of the factors leading to their success or failure. This book aims to meet such a need. It explains the scientific basis for surgery and considers the different diagnostic techniques that may be employed, thereby providing a better understanding of the surgical rationale, indications, and contraindications. The value of conservative options is also assessed to help the reader weigh the need for surgery. The various surgical modalities, including the most recent, are then fully described and evaluated with the aid of numerous illustrations. The book concludes with a chapter devoted to evidence-based analysis of the outcome of surgery in patients with low back pain. This book will be invaluable to orthopaedic and neurosurgeons, rheumatologists, neurologists, and all who are concerned with the effective treatment of this often debilitating condition.